A SURVEY ON LEAN MANUFACTURING IMPLEMENTATION: A CASE STUDY IN AN INDONESIAN AEROSPACE COMPANY - Eleonora Julianti Mardi Utami; Hotna Marina Sitorus (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Lean manufacturing is well-known worldwide, and many businesses today use it as a production method. However, many companies seem failed in the implementation. Therefore, the purpose of this paper is to assess lean performance in an Indonesian Aerospace Company and explore any factors that could drive and hinder the lean implementation from a holistic perspective. In essence, this research is rarely conducted in Indonesia, especially in the aerospace industry. LESAT (Lean Enterprise Self-Assessment Tools) V.2 questionnaire and methodology are adopted to assess lean implementation. The respondents were chosen with purposive sampling. The results showed that most of the evaluation activities related to the performance were done with an informal approach deployed in a few areas with varying degrees of effectiveness and sustainment. Furthermore, several factors are considered as driving and hindering to successful lean implementation. It was found that the driving factors for successful deployments are a good change agent, continuous improvement, involvement of suppliers in the supply chain, considerations of customer value, and evaluation of roles/programs for lean implementation. In comparison, the primary hinder factors are a lack of shared understanding of the company's condition among the managers and supervisor and between the other managers and directors, and culture.